Trip Attraction Model for Junior High School in Demak Regency - Putri, Ari Ananda; Salamatus Sa’ida, Fitriya (Jurnal Sosial Terapan, 2024)
School and work activities are one of the most dominant centers of travel movement in Indonesia. The presence of schools can attract people and vehicles. The attraction of travel will influence the increase in the number/volume of trips which can burden the road network. Educational land use will create quite large human movements for students and teachers and has the potential to disrupt the smooth flow of traffic in the school area. This research aims to identify the characteristics and identify models of travel attractions to junior high schools in Demak Regency. This research uses quantitative methods using secondary data. Analysis of the trip attraction model uses correlation tests, multiple linear regression tests and uses classical assumption tests. The results of the analysis show that the trip attraction to Junior High Schools in Demak Regency (Y) is influenced by the number of classes (X1), class capacity (X2), school size (X3) and number of supporting facilities (X4). The best model to predict the attraction of junior high school travel in Demak Regency is Y = 0.282 + 0.332 (X1) + 0.061 (X2) + 0,95 (X3) – 0.100 (X4) with an R² (Square) value of 0.854. The coefficient for the number of classes (X1) has a positive value, indicating that, assuming that there are no other independent variables, the tendency for travel attraction for junior high school land use (Y) has increased by 0.332 for every 1 unit increase in the number of classes. The class capacity coefficient (X2) is positive, indicating that assuming that there are no other independent variables, the tendency for travel attraction for junior high school land use (Y) to increase is 0.061 for every 1 unit increase in class capacity. The school area coefficient (X3) has a positive value, indicating that assuming that there are no other independent variables, the tendency for travel to use junior high school land (Y) will increase by 0.095 for every 1 unit increase in, school area. The coefficient for the number of supporting facilities (X4) is negative, indicating that assuming that there are no other independent variables, the tendency for travel attraction for SMP land use (Y) to decrease by 0.100 for every 1 unit increase in the number of supporting facilities.